Luminescence of Lanthanide Ions in Coordination Compounds and Nanomaterials. - De Bettencourt-Dias, Ana (Wiley, 2014)
This comprehensive book presents the theoretical principles, current applications and latest research developments in the field of luminescent lanthanide complexes; a rapidly developing area of research which is attracting increasing interest amongst the scientific community. Luminescence of Lanthanide Ions in Coordination Compounds and Nanomaterials begins with an introduction to the basic theoretical and practical aspects of lanthanide ion luminescence, and the spectroscopic techniques used to evaluate the efficiency of luminescence. Subsequent chapters introduce a variety of different app.